2019
DOI: 10.1051/0004-6361/201834713
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the dimming event of RW Aurigae A through multi-epoch VLT/X-shooter spectroscopy

Abstract: Context. RW Aur A is a classical T Tauri star that has suddenly undergone three major dimming events since 2010. The reason for these dimming events is still not clear. Aims. We aim to understand the dimming properties, examine accretion variability, and derive the physical properties of the inner disc traced by the CO ro-vibrational emission at near-infrared wavelengths (2.3 µm). Methods. We compared two epochs of X-Shooter observations, during and after the dimming. We modelled the rarely detected CO bandhea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 60 publications
4
39
0
Order By: Relevance
“…A slope in the extinction law flatter than that of the ISM and sometimes a nearly gray extinction have been reported for AA Tau, the prototype of dippers, by Bouvier et al (1999Bouvier et al ( , 2003 and for the dips of LkCa 15 by Alencar et al (2018). Koutoulaki et al (2019) were able to reproduce the extinction curve observed during a dimming event of RW Aur observed with X-shooter, which is much flatter than the ISM, with a power-law distribution of the grain size from a minimum value a min = 0.1 µm to a maximum a max = 150 µm, including the scattering in the effective optical depth. Neglecting the scattering would require even larger grains.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…A slope in the extinction law flatter than that of the ISM and sometimes a nearly gray extinction have been reported for AA Tau, the prototype of dippers, by Bouvier et al (1999Bouvier et al ( , 2003 and for the dips of LkCa 15 by Alencar et al (2018). Koutoulaki et al (2019) were able to reproduce the extinction curve observed during a dimming event of RW Aur observed with X-shooter, which is much flatter than the ISM, with a power-law distribution of the grain size from a minimum value a min = 0.1 µm to a maximum a max = 150 µm, including the scattering in the effective optical depth. Neglecting the scattering would require even larger grains.…”
Section: Discussionmentioning
confidence: 71%
“…In Fig. 3 we overplot the extinction model by Koutoulaki et al (2019), scaled to the observed extinction in the g band. We note that this curve is flatter than our data, suggesting different conditions for the region that causes the dips in ISO-ChaI 52, as is also expected based on the much deeper dips of RW Aur (2−3 mag in the V band) compared to 0.3 mag dips in r for ISO-ChaI 52.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We use a CO local thermodynamic equilibrium (LTE) model (see Koutoulaki et al 2019, for a detailed description of model, code and error estimates) to derive the main physical parameters of the gas. We model the CO bandhead profiles with a single ring in LTE with four free parameters: temperature T CO , column Notes.…”
Section: Co Physical Parametersmentioning
confidence: 99%
“…been proved to trace gas in Keplerian rotation very close to the star, very likely in the disc itself (Carr 1989;Kraus et al 2000;Bik & Thi 2004;Tatulli et al 2008;GRAVITY Collaboration 2020). By model-fitting the line profile of the CO bandhead emission obtained with high spectral resolution observations, several authors showed that the emission comes from a relatively warm (T ∼ 2000-5000 K) and dense gas (N CO ∼ 10 20 −10 22 cm −2 ) in Keplerian rotation (Carr 1989;Najita et al 1996;Ilee et al 2014;Koutoulaki et al 2019). However, this information has so far not been used to further constrain the physical, chemical, and thermal processes occurring in the inner disc.…”
Section: Introductionmentioning
confidence: 99%